Magyarország kultúrgeográfiai korszakai (895–1920) - Frisnyák, Sándor (Tér és Társadalom, 1996)
The conquering Hungarians as a semi-nomadic (livestock-keeping) and agrarian people settled down in the Carpathian Basin in 895-902, where they integrated into a nation and fit as an independent state into the system of the feudal nations of Europe. In the process of the changes in the way of life (and system), besides the fóllowing of models and inter-ethnic connections (e.g. adaptation of the medieval agrarian and handcraftship revolution), the innovative abilities, the autochtonous development and the traditional culture of the Hungarian people played an important role. The study summarises the basic features of the development of Hungarian society and eeonomy from the Hungarian conquest (895) until 1920, when the peace dictate of Trianon sliced the territory of historical Hungary.